Flexible Memristive Devices Based on InP/ZnSe/ZnS Core-Multishell Quantum Dot Nanocomposites - Kim, Do Hyeong; Wu, Chaoxing; Park, Dong Hyun; Kim, Woo Kyum; Seo, Hae Woon; Kim, Sang Wook; Kim, Tae Whan (ACS Applied Materials and Interfaces, 2018)
The effects of the ZnS shell layer on the memory performances of flexible memristive devices based on quantum dots (QDs) with an InP/ZnSe/ZnS core-multishell structure embedded in a poly(methylmethacrylate) layer were investigated. The on/off ratios of the devices based on QDs with an InP/ZnSe core-shell structure and with an InP/ZnSe/ZnS core-multishell structure were approximately 4.2 × 102 and 8.5 × 103, respectively, indicative of enhanced charge storage capability in the latter. After bending, the memory characteristics of the memristive devices based on QDs with the InP/ZnSe/ZnS structure were similar to those before bending. In addition, those devices maintained the same on/off ratios for retention time of 1 × 104 s, and the number of endurance cycles was above 1 × 102. The reset voltages ranged from -2.3 to -3.1 V, and the set voltages ranged from 1.3 to 2.1 V, indicative of reliable electrical characteristics. Furthermore, the possible operating mechanisms of the devices are presented on the basis of the electron trapping and release mode.
Keywords: Core shell structure; Electrical characteristic; Flexible device; Memory performance; memristive device; Multishell quantum dots; Multishell structures; Operating mechanism; flexible devices; InP/ZnSe/ZnS core-multishell quantum dots; memory device; memristive device; nanocomposites